Study of the migratory phenomenon Ecuador-United States: implications from international politics in the period 2018-2020. - Castillo Bravo, Cynthia Carolina (Revista Universidad de Guayaquil, 2022)
This research work was aimed at analyzing the Ecuador-United States migration phenomenon, considering theimplications from international politics in the 2018-2020 period, in order to propose an action plan that strengthens the protection and assistance of irregular immigrants. Ecuadorians. Each one of the actions taken allowed determining the impact of the immigration policy of the United States on the fundamental rights of Ecuadorian irregular immigrants. The methodology used was documentary, descriptive and the Analytical- Synthetic method was used. Likewise, the review of various bibliographic sources allowed to develop an exhaustive analysis of the study topic, considering both the neoclassical and socio-critical approach. Therefore,based on the documentary development and the opinions presented by the experts interviewed, it could be concluded that in recent years there has been evidence at an international level, a great legislative advance in the treatment of immigration. of the states for the protection of these rights have not been insufficient to solve the migratory problems that arise between Ecuador and the United States, reflecting deficiencies in the provision of public services or other damages under the condition of entry as irregular. In this way, through this research they proposed a series of international actions aimed at promoting the socio-economic inclusion of immigrants according to their needs.